Influence of artificial pinning centers on structural and superconducting properties of thick YBCO films on ABAD-YSZ templates - Pahlke, Patrick; Sieger, Max; Ottolinger, Rick; Lao, Mayraluna; Eisterer, Michael; Meledin, Alexander; Van Tendeloo, Gustaaf; Haenisch, Jens; Holzapfel, Bernhard; Schultz, Ludwig; Nielsch, Kornelius; Huehne, Ruben (Superconductor Science and Technology, 2018)
Recent efforts in the development of YBa2Cu3O7-x (YBCO) coated conductors are devoted to the increase of the critical current I c in magnetic fields. This is typically realized by growing thicker YBCO layers as well as by the incorporation of artificial pinning centers. We studied the growth of doped YBCO layers with a thickness of up to 7 μm using pulsed laser deposition with a growth rate of about 1.2 nm s-1. Industrially fabricated ion-beam textured YSZ templates based on metal tapes were used as substrates for this study. The incorporation of BaHfO3 (BHO) or Ba2Y(Nb0.5Ta0.5)O6 (BYNTO) secondary phase additions leads to a denser microstructure compared to undoped films. A purely c-axis-oriented YBCO growth is preserved up to a thickness of about 4 μm, whereas misoriented texture components were observed in thicker films. The critical temperature is slightly reduced compared to undoped films and independent of film thickness. The critical current density J c of the BHO- and BYNTO-doped YBCO layers is lower at 77 K and self-field compared to pure YBCO layers; however, I c increases up to a thickness of 5 μm. A comparison between films with a thickness of 1.3 μm revealed that the anisotropy of the critical current density J c(θ) strongly depends on the incorporated pinning centers. Whereas BHO nanorods lead to a strong B||c-axis peak, the overall anisotropy is significantly reduced by the incorporation of BYNTO forming a mixture of short c-axis-oriented nanorods and small (a-b)-oriented platelets. As a result, the J c values of the doped films outperform the undoped samples at higher fields and lower temperatures for most magnetic field directions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: coated conductors; pinning; YBCO